China's Proposed Maritime Silk Road: Challenges and Opportunities with Special Reference to the Bay of Bengal Region. (December 2015) - Karim, Mohd Aminul
Abstract : The aim of this article is to explore the challenges and opportunities of the 21st Century Maritime Silk Road – presumably a gigantic economic project launched by China – for better connectivity and economic cooperation in Asia. The article examines the variables that may either limit or bolster its implementation. The project, once implemented, is likely to give rise to both economic and strategic upshots. Economically, it is likely to be win–win for both China and other powers in Asia who are willing to participate. On the other hand, it may get trapped because of the presence of geopolitical issues and great powers rivalry, specifically in the Bay of Bengal region. The article, in the final analysis, attempts to provide certain policy prescriptions, mainly for China, for maximum optimization.